In situ interaction between the hormone 17α-ethynylestradiol and the liquid-ordered phase composed of the lipid rafts sphingomyelin and cholesterol - Ruiz, Gilia Cristine Marques [UNESP]; do Carmo Morato, Luis Fernando [UNESP]; Pazin, Wallance Moreira [UNESP]; Oliveira Jr, Osvaldo N.; Constantino, Carlos José Leopoldo [UNESP] (Elsevier, 2024)
Hormone treatments are frequently associated with cardiovascular diseases and cancers in women. Additionally, the detrimental effects of their presence as contaminants in water remain a concern. The transport of hormones through cell membranes is essential for their biological action, but investigating cell permeability is challenging owing to the experimental difficulty in dealing with whole cells. In this paper, we study the interaction of the synthetic hormone 17α-ethynylestradiol (EE2) with membrane models containing the key raft components sphingomyelin (SM) and cholesterol (Chol). The models consisted of Langmuir monolayers and giant unilamellar vesicles (GUVs) that represent bilayers. EE2 induced expansion of SM monolayers upon interacting with the non-hydrated amide group of SM head, but it had practically no effect on SM GUVs because these group are not available for interaction in bilayers. In contrast, EE2 interacted with hydrated phosphate group (PO2-) and amide group of SM/Chol mixture monolayer, which could explain the loss in phase contrast of liquid-ordered GUVs suggesting pore formation. A comparison with reported EE2 effects on GUVs in the fluid phase, for which no loss in phase contrast was observed, indicates that the liquid-ordered phase consisting of lipid rafts is relevant to be associated with the changes on cell permeability caused by the hormones.
Keywords: 17α-ethynylestradiol; Cholesterol; Giant unilamellar vesicles; Langmuir monolayers; PM-IRRAS; Rafts; Sphingomyelin